Fishbone Methodology: An Improved Goal-Oriented Framework for Requirements Engineering - Bano, Jameela; S. S. Reddy, L.; Khammari, Hedi (International Journal of Engineering and Technology, 2018)
Goals are a reasonable system intended for recognizing, arranging and mitigating software supplies. The word Goal is continuously used in Requirement Engineering (RE). Ended the historical ten years, the supplies manufacturing (RE) society consumes constantly extended hers acceptance then version of goal-oriented methods to equally useful and non-functional supplies (NFRs). Goal-Oriented obligation engineering (GORE) gives an imperceptible method aimed at elicitation, investigation, clarification & modification, pattern and modeling of requirements. Different methods of G.O.R.E are exists for these processes of requirement engineering based on confident underlying concepts and principles. Founded on our literature appraisal, we recognize that prevailing penalty area concerned with requirement elicitation procedure do not sustain to prioritize the supplies when the stakeholders view are frequently unclear and contain ambiguity. Therefore, we presented improved goal-oriented Approach called Fishbone Methodology for requirement engineering in this paper. The objective of this research article is to understand the needs of stakeholders and accordingly provide services to develop the increments of RE processes which results in building a prototype model of the software. We talk about goalmouths after the viewpoint of 2 themes: goal inspection and goal progression. Finally, our proposed method provides appropriate representation mechanisms to enhance stakeholder comprehension and facilitate communication between analysts and stakeholders.Â Â